2008
DOI: 10.1016/j.jad.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal reactions to environmental stress in elderly persons with anxiety disorders: Evidence from a population study of diurnal cortisol changes

Abstract: Background: Cortisol secretion in elderly persons with anxiety disorders exposed to common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…Subsequently, high levels of cortisol induced the volume reduction of the Hip, which is closely related to the impairment of explicit memory abilities (Monk et al, 2002). In addition, a neurophysiological study (Chaudieu et al, 2008) suggested that GAD symptoms were closely related to an increment of cortisol concentration. Furthermore, a structure-function correlation study (Harms et al, 2013) demonstrated a positive correlation between the GM volume of the Hip and functional activity during working memory recognition tasks in patients with psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, high levels of cortisol induced the volume reduction of the Hip, which is closely related to the impairment of explicit memory abilities (Monk et al, 2002). In addition, a neurophysiological study (Chaudieu et al, 2008) suggested that GAD symptoms were closely related to an increment of cortisol concentration. Furthermore, a structure-function correlation study (Harms et al, 2013) demonstrated a positive correlation between the GM volume of the Hip and functional activity during working memory recognition tasks in patients with psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has long been speculated that chronic elevations of stress-related hormones such as cortisol can weaken multiple physiological systems of older adults resulting in impaired cardiovascular and immune function, as well as contributing to dementia, and mood and anxiety disorders. Recently it has been reported that unlike elderly subjects without psychiatric disorder, elderly subjects with anxiety disorders showed a greater increase in cortisol secretion following exposure to a stressor (Chaudieu et al, 2008). Furthermore, while children and adolescents display elevated cortisol levels to persistent anxiety, associations between cortisol levels and anxiety disorders have not been reported (Greaves-Lord et al, 2007;Kallen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although this rate is less than depression patients, it indicates that there is also an abnormal response to stress in GAD patients and there is a defect in regulatory feedback mechanisms of HPA axis. There are reports stating that cortisol levels in GAD patients are low (6,7), normal (8) and-in elderly patients-high (9,10). In conclusion, findings on HPA axis abnormalities in PD and GAD appear to be conflicting and inadequate (11).…”
Section: Introductionmentioning
confidence: 82%